Social Justice and Sustainability of Peasant Family Farming - Ramón L. Espinel; Nayeth Solórzano (Revista Tecnológica, 2025)
Peasant family farming in Ecuador is responsible for producing over two-thirds of the food required to sustain the country's nutrition and significantly contributes to agricultural exports. Despite this, rural areas in Ecuador experience the highest levels of poverty, leading to widespread undernutrition, particularly among pregnant women and infants. This stark disparity presents a social justice issue that demands urgent attention. Some analysts argue that the inefficiencies of peasant agriculture contributes  these issues, labelling it as unsustainable due to its perceived low productivity and profitability. However, such assessments often overlook the sector's crucial role in food security, biodiversity preservation, and environmental balance. Family farming sustains local food supplies and promotes ecological stability through diverse, sustainable practices. Public policy orientation, particularly in support of small-scale farmers, is essential in determining these rural communities' sustainability and improved livelihoods, especially in the face of increasing pressures from modern corporate agriculture. Addressing these structural inequalities is key to ensuring that peasant family farming is economically viable, socially just, and environmentally sustainable.